2021
DOI: 10.5937/ekopre2108438r
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ecological responsibility on business excellence of mountain hotels

Abstract: Sustainable business management of companies aims to, taking into consideration all the goals of sustainable development, monitor and analyze business performance in order to be ready to react at the moment critical to the company's financial position. Risk management in sustainable business management refers to the implementation of ecological, social, and economic factors in a company's business. The focal point of the analysis are hotels from the mountain centers of Serbia, Bosnia and Herzegovina and Monten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Western Balkan region consists of the following countries: Serbia, North Macedonia, Albania, Montenegro and Bosnia and Hertzegovina. Radović and Čerović (2021) indicate that when evaluating the application of ecological principles within the framework of the analysed region, awareness of the use of renewable energy sources, as well as waste management, are at a very low level.…”
Section: Environmentally Responsible Operations In Hotel Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The Western Balkan region consists of the following countries: Serbia, North Macedonia, Albania, Montenegro and Bosnia and Hertzegovina. Radović and Čerović (2021) indicate that when evaluating the application of ecological principles within the framework of the analysed region, awareness of the use of renewable energy sources, as well as waste management, are at a very low level.…”
Section: Environmentally Responsible Operations In Hotel Industrymentioning
confidence: 99%
“…4 (2023) der for certain hotel companies to be considered eco-friendly from a social point of view. In order to meet the expectations of its guests, the hotel management must follow the events and trends in the global tourism market, as well as the processes of sustainable hotel management in order to permanently implement innovations and be competitive on the market (Radović & Čerović, 2021). There is a niche in the tourism market of sustainably educated tourists who practice activities related to environmentally sustainable engagement in their daily lives, which brings them benefits from the economic aspect.…”
Section: Environmentally Responsible Operations In Hotel Industrymentioning
confidence: 99%
“…An analysis of eco-responsibility, which represents one of the green criteria and its impact on business excellence, was performed in hotels in Serbia, Bosnia and Herzegovina and Montenegro [32]. The research showed that practising ecological activities did not affect the business excellence of the analysed hotels.…”
Section: Introductionmentioning
confidence: 99%